Activating Transcription Factor-5 Knockdown Reduces Aggressiveness of Mammary Tumor Cells and Attenuates Mammary Tumor Growth - Ben-Shmuel, Sarit; Rashed, Rola; Rostoker, Ran; Isakov, Elina; Shen-Orr, Zila; LeRoith, Derek (Frontiers in Endocrinology, 2017)
Activating transcription factor-5 (ATF5) is an anti-apoptotic factor, and has been implicated in enhancing the survival of cancer cells under stress and in regulating the autophagy process. Targeting ATF5 in anti-cancer therapy may be particularly attractive because of its differential role in cancer cells compared to non-transformed cells, thus allowing specificity of the treatment. Using the delivery of shRNA vectors into the Mvt1 and Met1 cell lines, we tested the role of ATF5 in the development of mammary tumors in vivo and in regulating proliferation and migration of these cells in vitro. In this study we demonstrate that knockdown of ATF5 in both cell lines results in decreased tumor volume and weight, as well as in reduced proliferation rate and migratory potential of the cells. In addition, knockdown of ATF5 led to increased autophagy flux and in a shift in the sub-populations comprising Mvt1 cells from the aggressive CD24-positive cells towards less aggressive CD24-negative. Taken together, these findings suggest that ATF5 plays an important role in enhancing mammary tumor cells overall aggressiveness and in promoting mammary tumor growth, and emphasize the possible benefit of anti-ATF5 therapy in breast cancer patients, particularly, against tumors characterized with positive expression of cell surface CD24.